APOE and Alzheimer’s Disease: From Lipid Transport to Physiopathology and Therapeutics - Husain, Mohammed Amir; Laurent, Benoit; Plourde, Mélanie (Frontiers in Neuroscience, 2021)
Alzheimer’s disease (AD) is a devastating neurodegenerative disorder characterized by extracellular amyloid β (Aβ) and intraneuronal tau protein aggregations. One risk factor for developing AD is the APOE gene coding for the apolipoprotein E protein (apoE). Humans have three versions of APOE gene: ε2, ε3, and ε4 allele. Carrying the ε4 allele is an AD risk factor while carrying the ε2 allele is protective. ApoE is a component of lipoprotein particles in the plasma at the periphery, as well as in the cerebrospinal fluid (CSF) and in the interstitial fluid (ISF) of brain parenchyma in the central nervous system (CNS). ApoE is a major lipid transporter that plays a pivotal role in the development, maintenance, and repair of the CNS, and that regulates multiple important signaling pathways. This review will focus on the critical role of apoE in AD pathogenesis and some of the currently apoE-based therapeutics developed in the treatment of AD.